Exploring the Integration of Artificial Intelligence in English Writing: A Library Research - Ni Putu Ayu Pirdayanti; I Kadek Dony Suantika; I Ketut Andika Pradnyana (SENTRI: Jurnal Riset Ilmiah, 2026)
Writing is a fundamental ability that is crucial for communication, education, and social impact. It is the potential, particularly in the areas of the environment and education. It is in line with the notion that writing is the process of conveying ideas, sentiments, and thoughts through a spoken or written system meant for people who belong to a particular linguistic community. Some students lack the self-assurance and will to write, and they also need to learn grammar, punctuation, vocabulary, and diction, the most important components of writing. In this technology-driven era, learning can be accessed in various ways; one such method is the use of technology to learn writing. Artificial intelligence (AI) can be used to improve the expressive and interactive aspects of writing instruction. Some AI-powered programs allow students to create, edit, and improve their texts through personalized recommendations and instant feedback. This study used a library research methodology. Journals, books, papers, library research, theses, and proceeding journals were the sources of the information. The reviews claims that a variety of AI and technical tools can help students write in English more rapidly and precisely. Some of the tools including Chat GPT, Grammarly, QuillBot, and Turnitin. Some AI-powered tools allow students to create, edit, and improve their texts through personalized recommendations and instant feedback. Fortunately, by incorporating contemporary technology, these enduring writing difficulties can be greatly reduced in our quickly developing digital age.